Indigenous Intellectuals, History Writing and Native Epistemes - Fontenla, Manuel (2024)
The following article aims to analyze some epistemic keys in the way in which indigenous Diaguita intellectuals approach the writing of history. These writings put into play, on the one hand, the ethnic identity of the indigenous intellectual and the question about the subject and the place of enunciation from which his epistemic-political positioning is constructed. On the other hand, they propose a project of criticism and decolonization of history, to the extent that their writings propose a direct and open confrontation with the hegemonic (colonial) versions of history. From these two dimensions, we are interested in reflecting on the possibility that these writings configure a native episteme for the rewriting and rereading of indigenous history.